A study to determine the change in porosity indicators of the shoe upper hinge in technology processes - Khamitov, Ali (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In the processes of technology in the processing of leather raw materials, the shoe upper hinge is used to confirm the micropore, mesopore, porous radius and porosity indicators, and changes in the physical and chemical properties of shoe upper hinge depending on the technology in the processing of leather raw materials.